Partition regularity of Pythagorean pairs - Nikos Frantzikinakis; Oleksiy Klurman; Joel Moreira (Forum of Mathematics, Pi)
We address a core partition regularity problem in Ramsey theory by proving that every finite coloring of the positive integers contains monochromatic Pythagorean pairs (i.e.,